2016
DOI: 10.17507/tpls.0609.19
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Relationship between Translation Studies Students’ Critical Thinking Ability and the Quality of Literary Prose Text Translation

Abstract: Abstract-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The current research aligns with the results of several previous studies concerning the direct impact of critical thinking on the translation technology proficiency of college students (Azin & Tabrizi, 2016;Ghaemi & Sadoughvanini, 2020;Jahromi & Suzani, 2016;Liu, 2019;Parham & Fahim, 2013). These studies found a positive correlation between the critical thinking and translation performance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current research aligns with the results of several previous studies concerning the direct impact of critical thinking on the translation technology proficiency of college students (Azin & Tabrizi, 2016;Ghaemi & Sadoughvanini, 2020;Jahromi & Suzani, 2016;Liu, 2019;Parham & Fahim, 2013). These studies found a positive correlation between the critical thinking and translation performance.…”
Section: Discussionsupporting
confidence: 90%
“…Azin and Tabrizi (2016) also found a positive relationship between critical thinking skills. Other studies, such as Jahromi and Suzani (2016) further supported this association, showing that critical thinking, particularly deductive and inductive reasoning, significantly predicts translation performance. Ghaemi and Sadoughvanini (2020) extended this understanding, correlating higherorder thinking skills, including analyzing and creating, with translation quality.…”
Section: Critical Thinking and Translationmentioning
confidence: 65%
“…Furthermore, the results of the present study were in accordance with studies mentioned in the literature review section, in that it revealed a moderate positive correlation between overall translation ability and critical reading skill (r = .65, p.01). However, the earlier studies found a wide range of degree of relationship between translation ability and reading comprehension skill (r = .30 -.91, at least ps.05) (Aminafshar, 2016;Dwi, 2014;Jahromi & Suzani, 2016;Kavaliauskiene & Kaminskiene, 2009;Khanmohammad & Kehtari, 2015;Mashhadi, 2008;Pham, 2017;Rahemi & Jurif, 2013;Tavakoli, Shafiei & Hatam, 2012;Widiasari et al, 2015).…”
Section: Relationship Between Critical Reading and Translation Abilitymentioning
confidence: 98%
“…Some affective factors, such as reading habit, and writing interests were proposed as the variables that might be related to translation ability (Hernandani, 2015;Ridhwan, 2014). Another group of researchers focused their attention on cognitive factors such as critical thinking ability (Jahromi & Suzani, 2016), vocabulary mastery (Khotimah, 2015), writing skill (Hernandani, 2015), and reading comprehension skill (Kavaliauskiene & Kaminskiene, 2009;Mashhadi, 2008;Rahemi & Jufri, 2013;Widiasari, Supraman, & Sudirman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They argued that critical thinkers not only outperform in inspecting the message of source language text but also synthesize it more efficiently. Jahromi and Suzani (2016) used Ricketts Critical Thinking Ability questionnaire (2003) to elicit learners’ critical thinking skill. In order to assess learners’ translation quality, they also used Vinay and Darbelnet’s model, which presented two strategies of translation: direct and oblique.…”
Section: Review Of Literaturementioning
confidence: 99%